Postoperative delayed gastric emptying: may gut microbiota play a role? - Wang, Zhiyi; Liu, Chuanbo; Hu, Kaiwen; Zuo, Minghuan; Tian, Zhen; Wei, Yue (Frontiers in Cellular and Infection Microbiology, 2024)
Postoperative delayed gastric emptying is a prevalent complication following surgical procedures, imposing heavy physical and financial burdens on patients. However, current treatment options remain suboptimal. In recent years, an increasing number of studies have highlighted that the gut microbiota and its metabolites are closely associated with postoperative complications. Various factors can disrupt the gut microbiome after surgery. This review discusses the potential mechanisms by which the gut microbiota and their metabolites may contribute to the pathogenesis of postoperative delayed gastric emptying. However, the current knowledge base is limited in terms of fully understanding the exact mechanisms involved. It is therefore evident that further research is required to fully elucidate the role of the gut microbiome in postoperative delayed gastric emptying, with the aim of uncovering new possibilities for preventive measures and therapeutic treatments.